(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic caused abrupt changes in the routine of the world population, which generated adaptive needs that are not always assimilated in a healthy way by everyone. For this reason, reports of disorders, emotional and physical are frequent and with different intensities in the most varied groups. Among the most common manifestations are changes in sleep and the level of stress. The objectives of these study were to evaluate the stress and sleep quality profile of dentistry students after a month of social isolation and the influence of these variables on the study routine. Material and Methods: This is a cross-sectional observational study applied in dental students using Google Forms. The dates were obtained by a socio-demographic questionnaire and assessment instruments on the Pittsburgh Sleep Quality Index, Epworth’s Sleepiness Scale, and Cohen’s Perceived Stress Scale. Results: About 62.5% of the 136 students evaluated had poor quality of sleep. Their stress levels were high, with a median of 32. The study routine was compromised in 62.5% of the students. Conclusion: The stress induced low quality of sleep and directly interfered with the subjects’ study routine, thereby establishing a cause-and-effect relationship.